The new British politics - Budge, Ian. (Harlow : Pearson Longman, 2007)
This fourth edition offers an introduction to current British politics. It combines incisive and original analysis with clear and direct presentation, specially tailored to the needs of lecturers, teachers and students of British politics from A-level to University Second Year.
Includes index.
Previous ed.: 2004.
Includes bibliographical references and index.
Keywords: Great Britain. -- Parliament -- Elections; Elections -- Great Britain; Political parties -- Great Britain; Great Britain -- Politics and government -- 1997-